2012
DOI: 10.1038/mt.2012.150
|View full text |Cite
|
Sign up to set email alerts
|

A TLR and Non-TLR Mediated Innate Response to Lentiviruses Restricts Hepatocyte Entry and Can be Ameliorated by Pharmacological Blockade

Abstract: Lentiviral vector (LV)-mediated gene transfer is a promising method of gene therapy. We previously reported that systemic injection of HIV-based LV triggers a transient inflammatory response. Here, we carried out studies to better characterize this response, and to develop a strategy to overcome the adverse effects of interferon (IFN) on LV-mediated gene transfer. We profiled gene expression in the liver after LV administration using deep-sequencing (RNA-seq), and identified several innate response pathways. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…In vivo administration of LV triggers type I interferon (IFN) responses that restrict gene transfer and promote vector clearance (13). Consistent with previous in vitro findings, this mechanism was shown to be partially dependent on TLR7, which senses the ssRNA genome of LV (14, 136, 137). However, TLR-independent innate immune responses were detected as well (14).…”
Section: Gene Therapies For Hemophlia Bsupporting
confidence: 91%
See 1 more Smart Citation
“…In vivo administration of LV triggers type I interferon (IFN) responses that restrict gene transfer and promote vector clearance (13). Consistent with previous in vitro findings, this mechanism was shown to be partially dependent on TLR7, which senses the ssRNA genome of LV (14, 136, 137). However, TLR-independent innate immune responses were detected as well (14).…”
Section: Gene Therapies For Hemophlia Bsupporting
confidence: 91%
“…For instance, preclinical studies with LV vectors have revealed that innate immune responses involving type I interferon (IFN) production can lead to impaired transgene expression and CD8 + T cell responses against the transgene (13, 14). Clinical trials of AAV-mediated gene transfer have also revealed the detrimental impact of pre-existing immunity to the AAV capsid, both in regards to neutralizing antibodies (NAB) preventing transduction as well as a memory CD8 + T cell response to the viral capsid that can eliminate transduced hepatocytes (15).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings corroborate that cell proliferation is an important determinant in supporting RRV replication and, unlike VSV and other oncolytic viruses and lentiviral vectors, RRVs do not induce cellular innate immune activity in cell cultures. Recent findings by Agudo et al demonstrated that lentiviral vectors can activate the innate response in the liver via a TLR-independent pathway (43). It is still likely that there is an in vivo mechanism of type I IFN induction, other than through the cells studied here, that suppresses viral replication in normal tissue and yet allows for the tumor-specific replication observed in some mouse tumor models and in dogs and humans with gliomas.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, although initial studies conducted in a human B cell line showed remarkably low impact of LV transduction on cellular gene expression [28], recent reports indicate that LVs activate myeloid dendritic cells (DC) through TLR 3 and 7 [29,30]. Transduction has also been reported to trigger TLR-dependent and independent innate signaling in murine hepatocytes, leading to decreased transduction [31]. Along these lines, inhibition of TLR signaling in human Natural Killer (NK) cells can lead to improved transduction [32].…”
Section: Innate Sensing Of Lentiviral Transductionmentioning
confidence: 99%